Calcium Permeable Channels in Cancer Hallmarks - Tajada, Sendoa; Villalobos, Carlos (Frontiers in Pharmacology, 2020)
Cancer, the second cause of death worldwide, is characterized by several common criteria, known as the “cancer hallmarks” including unrestrained cell proliferation, cell death resistance, invasion and metastasis, and angiogenesis. Ca2+ permeable channels are proteins present in external and internal biological membranes, diffusing Ca2+ ions down their electrochemical gradient. Numerous physiological functions are mediated by Ca2+ channels, ranging from Ca2+ homeostasis to sensory transduction. Consequently, Ca2+ channels play important roles in human physiology and it is not a surprise the increasing number of evidences connecting Ca2+ channels disorders with tumor cells growth, survival and migration. Multiple studies suggest that Ca2+ signals are augmented in various cancer cell types, contributing to cancer hallmarks. This review focuses in the role of Ca2+ permeable channels signaling in cancer with emphasis on the mechanisms behind the remodeling of the Ca2+ signals. The Store-Operated Channels (SOC) and Transient Receptor Potential (TRP) channels are the main extracellular Ca2+ source in the plasma membrane of non-excitable cells, while inositol trisphosphate receptors (IP3R) are the main channels releasing Ca2+ from the endoplasmic reticulum (ER). Alterations in the activity and/or expression of these Ca2+ channels, as wells as, the Ca2+ buffering by mitochondria affect intracellular Ca2+ homeostasis and signaling, contributing to the transformation of normal cells into their tumor counterparts. Several compounds reported to counteract several cancer hallmarks also modulate the activity and/or the expression of these channels including non-steroidal anti-inflammatory drugs (NSAIDs) like aspirin and sulindac, and inhibitors of polyamine biosynthesis, like difluoromethylornithine (DFMO). The possible role of the Ca2+ permeable channels targeted by these compounds in cancer and their action mechanism will be discussed also in the review.